A Scoping Review of Qualitative Research Methods Used With People in Prison. Issue 1 (22nd October 2018) - Abbott, Penelope; DiGiacomo, Michelle; Magin, Parker; Hu, Wendy
Researchers undertaking qualitative interview and focus group research with people in prison must consider the research methods they use, given the ethical and practical complexities of prison-based research. In particular, there are explicit and implicit coercion risks and barriers to access, privacy, and confidentiality. To examine how the challenges of conducting rigorous qualitative research with prisoners were handled, we undertook a scoping review of recruitment and data collection processes reported in qualitative research with prisoners. We searched for peer-reviewed articles of qualitative interview and focus group research with adult prisoners, published in the English language from 2005 to 2017, using MEDLINE, Embase, PsycINFO, and CINAHL databases. There were 142 articles reporting on 126 studies which met the review inclusion criteria. Challenges related to coercion risk, participant recruitment, sampling, confidentiality, privacy, and working with prison-based intermediaries should be explicitly addressed and reported. Our findings highlight key considerations and contextualized strategies for recruitment and data collection for researchers who seek to conduct rigorous and ethical qualitative research with prisoners.